Does tai chi improve psychological well-being and quality of life in patients with cardiovascular disease and/or cardiovascular risk factors? A systematic review - Guoyan Yang; Wenyuan Li; Nerida Klupp; Huijuan Cao; Jianping Liu; Alan Bensoussan; Hosen Kiat; Diana Karamacoska; Dennis Chang (BMC, 2022)
Abstract Background Psychological risk factors have been recognised as potential, modifiable risk factors in the development and progression of cardiovascular disease (CVD). Tai Chi, a mind-body exercise, has the potential to improve psychological well-being and quality of life. We aim to assess the effects and safety of Tai Chi on psychological well-being and quality of life in people with CVD and/or cardiovascular risk factors. Methods We searched for randomised controlled trials evaluating Tai Chi for psychological well-being and quality of life in people with CVD and cardiovascular risk factors, from major English and Chinese databases until 30 July 2021. Two authors independently conducted study selection and data extraction. Methodological quality was evaluated using the Cochrane Risk of Bias tool. Review Manager software was used for meta-analysis. Results We included 37 studies (38 reports) involving 3525 participants in this review. The methodological quality of the included studies was generally poor. Positive effects of Tai Chi on stress, self-efficacy, and mood were found in several individual studies. Meta-analyses demonstrated favourable effects of Tai Chi plus usual care in reducing anxiety (SMD − 2.13, 95% confidence interval (CI): − 2.55, − 1.70, 3 studies, I 2  = 60%) and depression (SMD -0.86, 95% CI: − 1.35, − 0.37, 6 studies, I 2  = 88%), and improving mental health (MD 7.86, 95% CI: 5.20, 10.52, 11 studies, I 2  = 71%) and bodily pain (MD 6.76, 95% CI: 4.13, 9.39, 11 studies, I 2  = 75%) domains of the 36-Item Short Form Survey (scale from 0 to 100), compared with usual care alone. Tai Chi did not increase adverse events (RR 0.50, 95% CI: 0.21, 1.20, 5 RCTs, I 2  = 0%), compared with control group. However, less than 30% of included studies reported safety information. Conclusions Tai Chi seems to be beneficial in the management of anxiety, depression, and quality of life, and safe to practice in people with CVD and/or cardiovascular risk factors. Monitoring and reporting of safety information are highly recommended for future research. More well-designed studies are warranted to determine the effects and safety of Tai Chi on psychological well-being and quality of life in this population. Systematic review registration International Prospective Register for Systematic Reviews (PROSPERO), CRD42016042905. Registered on 26 August 2016.